Worthy opponents : a novel - Steel, Danielle (New York, NY : Random House Large Print, 2023)
Spencer Brooke always knew she was destined to be CEO of her grandfather's business-the most respected and luxurious department store in New York City. Brooke's has been at the center of every happy memory she has, but it hasn't been an easy journey. Seven years after her father's death, her life is very different from the days when she walked through the store with her grandfather as a young girl.
Keywords: Large type books; Department stores -- Fiction; Inheritance and succession -- Fiction; Divorced women -- Fiction; Single mothers -- Fiction; Families -- Fiction; Man-woman relationships -- Fiction; New York (N.Y.) -- Fiction